Artemether-Lumefantrine versus Dihydroartemisinin-Piperaquine for Treating Uncomplicated Malaria: A Randomized Trial to Guide Policy in Uganda - Yeka, Adoke (Public Library of Science, 2008)
BACKGROUND: Uganda recently adopted artemether-lumefantrine (AL) as the recommended first-line treatment for uncomplicated malaria. However, AL has several limitations, including a twice-daily dosing regimen, recommendation for administration with fatty food, and a high risk of reinfection soon after therapy in high transmission areas. Dihydroartemisinin-piperaquine (DP) is a new alternative artemisinin-based combination therapy that is dosed once daily and has a long post-treatment prophylactic effect. We compared the efficacy and safety of AL with DP in Kanungu, an area of moderate malaria transmission. METHODOLOGY/PRINCIPAL FINDINGS: Patients aged 6 months to 10 years with uncomplicated falciparum malaria were randomized to therapy and followed for 42 days. Genotyping was used to distinguish recrudescence from new infection. Of 414 patients enrolled, 408 completed follow-up. Compared to patients treated with artemether-lumefantrine, patients treated with dihydroartemisinin-piperaquine had a significantly lower risk of recurrent parasitaemia (33.2% vs. 12.2%; risk difference = 20.9%, 95% CI 13.0–28.8%) but no statistically significant difference in the risk of treatment failure due to recrudescence (5.8% vs. 2.0%; risk difference = 3.8%, 95% CI −0.2–7.8%). Patients treated with dihydroartemisinin-piperaquine also had a lower risk of developing gametocytaemia after therapy (4.2% vs. 10.6%, p = 0.01). Both drugs were safe and well tolerated. CONCLUSIONS/SIGNIFICANCE: DP is highly efficacious, and operationally preferable to AL because of a less intensive dosing schedule and requirements. Dihydroartemisinin-piperaquine should be considered for a role in the antimalarial treatment policy of Uganda. TRIAL REGISTRATION: Controlled-Trials.com ISRCTN75606663